Analisis Efektivitas Biaya Distribusi Lumsum Terhadap Pendapatan (Studi Kasus di PT. Indofresh cabang Jakarta) - Panca Fanus; Iis Dewi Herawati (Universitas Indraprasta PGRI, 2021)
In the retail business, distribution costs as a major cost component that greatly affect a company's profit or loss. PT. Indofresh as the largest importer and distributor of fresh fruit and vegetable products in Indonesia that faces high distribution costs and also often late return letters as a means of billing has a severe impact on the company's financial activities. So the company carried out an efficiency initiative by changing the pattern of distribution costs from distribution costs paid upfront to lumpsum distribution costs applied in Jakarta. This research uses quantitative and qualitative methods. The purpose of this research will be to study the effectiveness and impact that will be caused by the application of these costs so that in the future it will be useful for companies for application in other branches or can be used in other companies. In the end, this study proves that efficiency can be achieved by applying lumpsum distribution costs can achieve efficiency of up to 20%, proof of return letter or pod (proof of delivery) increases by more than 20%, the process of billing credit sales and the effectiveness of the work of related parts becomes faster.